Chronique juridique - Moreau, Rémi (Assurances, 1984)
The author studies a number of cases concerning automobile insurance, as well as the lime limits for bringing actions for damages against engineers, architects and contractors. He looks at various legal decisions as they affect automobile multi-peril coverage. Also considered are the insurable interest of a notary practicing on his own, and the description of risk and the insurer's joint liability under the terms of article 2585 of the Civil Code. Finally, the author looks at the effect of mortgage clauses as they apply to the insured and the mortgage.